Pochodzenie i poczucie wspólnoty regionalnej wśród mnichów na Pustyni Judzkiej w V i VI wieku - na podstawie ,,Żywotów mnichów palestyńskich? Cyryla ze Scytopolis = - Twardowska, Kamilla (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The work by Ciri of Scythopolis titled 'The lives of Monks of Palestine' is an irreplacable source of knowledge to reveal a range of aspects connected with the beginning and flourishing of monasticism in he Judaean Desert. Palestinian monasticism, multi-ethnic in its source, managed to preserve its cosmpolitism at the time of its greatest development that took place in 6th century. Monks came from area of whole Empire, however among monks in the Judaean Desert, there dominated those who derived from Asia Minor and other areas of the eastern part of the Empire. We easily notice both regional and family bond among them.
Keywords: Cyryl ze Scytopolis (mnich; 524-599); monastycyzm; Pustynia Judzka; 5 w.; 6 w.